Kamisama kiss. Vol. 9 - Suzuki, Julietta (Shojo beat manga., 2012)
"Nanami may have been (begrudgingly) accepted by the other kami at Izumo, but that doesnt make her any less human or help her deal with her growing feelings for Tomoe. Should she be true to her heart or cut Tomoe loose for his own good? Either way, getting dragged into a group date isnt going to help matters at all"--Page 4 of cover.